The relationship of socioeconomic and household food security among smallholder glutinous rice famers in Langkawi, Malaysia - Wardani, Nur Afifah Septiana Jayanti Eka; Jamaluddin, Askiah; Zainal Badari, Shamsul Azahari; Zainalaludin, Zumilah; Hamsan, Hanina Halimatusaadiah; Samdin, Zaiton (Malaysian Association of Consumer and Family Economics (MACFEA), 2023)
Smallholder farmers are a group that is vulnerable to food insecurity due to the various challenges they face, such as low income, natural disasters, and relatively remote living areas. This study aims to explore the relationship between socioeconomic status and household food security among smallholder glutinous rice farmers in Langkawi, Malaysia. The research will employ a quantitative approach, using Household Insecurity Access Scale (HFIAS). Analyze the linkages, using correlation and multiple regression, between the respondent’s income, respondent’s education, the age of the household head, wife’s income, land size, and household food security. In this study, it was found that there were several groups such as food secure (64.9%), mildly f The prevalence of food insecurity (mildly, moderately, severely) among respondents was 30.5% or 3.5 out of 10 people. Food insecure (15.2%), moderate food insecure (12%), and severely food insecure (5.1%). The research results show that the respondent’s income (p=0.000**), the respondent’s education (p=0.008**), and the wife’s income (p=0.045*) are variables that have a relationship with household food insecurity. In conclusion, the result showed that the respondent’s income, the respondent’s education, and the wife’s income have relationship with food security. In its application the author recommends, the relationship between socioeconomic variables and household food security can be a guide for governments, non- profit organizations and related institutions to make policies.